"An Expanded Window of Understanding a Changed Everyday Life"—Experiences From Patients With Long-Term Conditions After Attending Group Learning Sessions. (December 2020) - Lindblad, Anna; Hedberg, Berith; Nygårdh, Annette; Petersson, Christina
Objective: Health education programs using group learning sessions for patients with long-term conditions have been tested, but not evaluated. In order to evaluate such sessions, the purpose was to explore experiences from patients with long-term conditions after participating in group learning sessions. Methods: A descriptive design based on qualitative content analysis was used. Interviews were conducted with 19 patients with different long-term conditions, and participants were asked about their experiences after taking part in the group learning sessions. Results: Sharing experiences with one another gave them opportunities for learning. Patients described a metaphorical "expanded window, " which opens in the group learning sessions; comparable to encounters during regular visits to health care providers. The nature of the learning environment that follows the educational model, together with describing lived experiences, allowed patients to share capability and resources, which was found to be foundational. Conclusions: The health education program as a format was important for shared learning. The facilitator can support the learning by structuring the format, but most essential was sharing experiences that facilitated each patient's learning that can aid the support of individual self-management.